Politeness Strategy Used by Tour Guides in Borobudur Tourism Areas: A Pragmatic Study - Sesanti, Indah - (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2023)
This research aims to describe the politeness strategy of the tourism practitioner which is tour guides in Borobudur tourism areas. Thus, in tourism industry tourist act as a gust and tour guides as a host, in which typically tourism practitioners will try to act politely and follow the politeness strategies as possible when they serving to tourist to ensure their satisfaction. The level of satisfaction can be determined by the politeness strategies of their behavior used towards the guests including the politeness strategy of their tourism service language. This research was done in Borobudur tourism areas, the main tourist destination in Magelang, Central Java. People can further strengthen their social relationships and respect each other's self-image by emphasizing polite communication. Through direct conversations with tourists from other countries, unique informal learning results in speech variations in English that are distinct from standard English rules. The purpose of this qualitative, descriptive, and conversational analysis study is to describe the linguistic phenomena pertaining to politeness strategies in the English variation of tour guides. This research method used a qualitative research design. Data collection technique were carried out through field observation, document review. Data analysis technique were based on the Brown and Levinson theory with conversational analysis. The result show that from speech data of positive and negative face. In data positive politeness that found 13 and 15 for negative positive politeness included hedging. The use of grammatical and lingual markers in the speech of tourism practitioners such as the use of the word (maybe, thank you, yes, good, may, like that, that’s it ...) become a model of politeness in the language of tourism practitioners in the Borobudur tourism areas.Keywords— Politeness Strategy, Politeness marker, Conversational Analysis, Tour guides.